2011
DOI: 10.1002/jbm.b.31782
|View full text |Cite
|
Sign up to set email alerts
|

A 3D numerical simulation of stress distribution and fracture process in a zirconia‐based FPD framework

Abstract: In this study, a numerical approach to the fracture behavior in a three-unit zirconia-based fixed partial denture (FPD) framework was made under mechanical loading using a newly developed three-dimensional (3D) numerical modeling code. All the materials studied were treated heterogeneously and Weibull distribution law was applied to describe the heterogeneity. The Mohr-Coulomb failure criterion with tensile strength cut-off was utilized to judge whether the material was in an elastic or failed state. For valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
3
7
0
Order By: Relevance
“…In the present study the main fracture mechanism in the three-unit c-FPD framework could be identified as tensile stress failure and the crucial location for fracture was identified as being in the gingival embrasure. These findings are in agreement with those in previous numerical simulation analyses (Kelly , 1995;Kou et al, 2007;Dittmer et al, 2009;Kou et al, 2011). However, one unique feature in the present 3D numerical simulation is the possibility it offers to follow the whole fracture process from beginning to end (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the present study the main fracture mechanism in the three-unit c-FPD framework could be identified as tensile stress failure and the crucial location for fracture was identified as being in the gingival embrasure. These findings are in agreement with those in previous numerical simulation analyses (Kelly , 1995;Kou et al, 2007;Dittmer et al, 2009;Kou et al, 2011). However, one unique feature in the present 3D numerical simulation is the possibility it offers to follow the whole fracture process from beginning to end (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Comparison the results obtained in the earlier 3D numerical simulation study (Kou et al, 2011) with a previous laboratory test (Sundh et al, 2005) reveals that the fracture patterns in the numerical study and the laboratory test were in agreement with each other. In both studies the fracture went between one of the connectors and diagonally through the loading point and no fracture could be observed in the abutments.…”
Section: Validation Of the Numerical Simulationsupporting
confidence: 72%
See 3 more Smart Citations